Science Fiction and Technoculture Studies Program at UC Riverside. - Latham, Rob; Vint, Sherryl (Science Fiction Studies, 2013)
The article offers information on the new Science Fiction and Technoculture Studies (SFTS) program to be launched at the University of California, Riverside starting in Fall 2013. The program will examine the intersections linking science-fiction studies, science and technology studies (STS), and technoculture studies. The program will also address issues on the role of popular culture and the genre of science fiction, particularly in mediating public understandings of science.